Smart Technologies for Precision Assembly: 9th IFIP WG 5. 5 International Precision Assembly Seminar, IPAS 2020, Virtual Event, December 14-15, 2020, Revised Selected Papers - Ratchev, Svetan (Springer International Publishing AG, 2021)
This open access book constitutes the refereed post-conference proceedings of the 9th IFIP WG 5.5 International Precision Assembly Seminar, IPAS 2020, held virtually in December 2020.The 16 revised full papers and 10 revised short papers presented together with 1 keynote paper were carefully reviewed and selected from numerous submissions.